2015
DOI: 10.1200/jco.2014.57.1513
|View full text |Cite
|
Sign up to set email alerts
|

Primary Results of ROSE/TRIO-12, a Randomized Placebo-Controlled Phase III Trial Evaluating the Addition of Ramucirumab to First-Line Docetaxel Chemotherapy in Metastatic Breast Cancer

Abstract: Purpose Currently, antiangiogenic strategies in metastatic breast cancer have demonstrated modest improvements in progression-free survival (PFS) but not improved quality or duration of survival, warranting evaluation of new agents in a placebo-controlled setting. Ramucirumab is a human immunoglobulin G1 antibody that binds vascular endothelial growth factor receptor-2 and blocks ligand-stimulated activation. The ROSE/TRIO-012 trial evaluated ramucirumab with docetaxel in unresectable, locally recurrent, or me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(80 citation statements)
references
References 23 publications
1
76
0
3
Order By: Relevance
“…In some of these studies results of the prior phase I clinical trials were considered sufficiently promising to conduct phase III RCTs (35)(36)(37)(38). Furthermore, investigators sometimes justified evaluation of a new anticancer therapy on the basis of preclinical data, or on results of RCTs, which evaluated the same treatment in different cancer types (39). In recent published reports of RCTs, investigators openly stated that results of phase II trials were not available when phase III RCTs were initiated (40,41).…”
Section: An Example Of Failed Drugs-inhibitors Of Angiogenesismentioning
confidence: 99%
“…In some of these studies results of the prior phase I clinical trials were considered sufficiently promising to conduct phase III RCTs (35)(36)(37)(38). Furthermore, investigators sometimes justified evaluation of a new anticancer therapy on the basis of preclinical data, or on results of RCTs, which evaluated the same treatment in different cancer types (39). In recent published reports of RCTs, investigators openly stated that results of phase II trials were not available when phase III RCTs were initiated (40,41).…”
Section: An Example Of Failed Drugs-inhibitors Of Angiogenesismentioning
confidence: 99%
“…However, in metastatic, human epidermal growth factor receptor 2-negative (HER2-negative) breast cancer, results have been somewhat disappointing. In the ROSE/TRIO trial, ramucirumab in combination with docetaxel failed to demonstrate a meaningful improvement in important clinical outcomes versus docetaxel alone (OS: 27.3 vs. 27.2 months; HR: 1.01; 95% CI: 0.83-1.23; p 5 .915) [34]. Phase III trials of ramucirumab are also ongoing in mCRC, and results of its use in advanced hepatocellular carcinoma (HCC) as a second-line treatment (REACH trial) have been presented recently [35].…”
Section: Afliberceptmentioning
confidence: 99%
“…The variability in response to antiangiogenic therapy in breast cancer is most likely explained by the extent of vascularization in this tumor type, the highly heterogeneous nature of the disease, the development of drug resistance, and the utilization of compensatory angiogenic mechanisms [17]. Recent results with ramucirumab plus docetaxel in the ROSE/TRIO trial in advanced HER2-negative breast cancer were disappointing [34].Nomeaningful improvementin importantclinical outcomes such as OS versus docetaxel alone were observed, and there was significantly more toxicity [34]. However, results from the TANIA and IMELDA trials in this indication demonstrated that continued second-line treatment with bevacizumab plus chemotherapy significantly improved PFS compared with bevacizumab alone [143,144].…”
Section: Wwwtheoncologistcom ©Alphamed Press 2015mentioning
confidence: 99%
“…In these poor prognosis diseases, even a small absolute survival benefit of two months is clinically valuable. Disappointing clinical results reported for the ROSE study confirm that breast cancer may limitedly benefit from angiogenic inhibitors (Mackey et al, 2014). While ongoing studies will clarify the role of ramucirumab in metastatic colorectal cancer, translational research will provide more details about how to properly select optimal candidates and corroborate the ethnical difference in benefit.…”
Section: Therapeutic Implications and Updates On The Clinical Advancementioning
confidence: 94%